The Discourse of Love in Literature (Based on the Novel by Eric Schmitt "Les Perroquets de la Place d’Arezzo") - Вдовиченко, Елизавета Анатольевна; Lushnikova, Galina (Philology & Human, 2019)
article deals with the study of the artistic discourse, which has verities of sub-discourses. In this case, we investigate discourse of love. The authors discuss the peculiarities of the discourse of love as represented in the postmodernist fiction of the XXI century on the basis of the novel Les Perroquets de la Place d’Arezzo by a famous French writer Eric-Emmanuel Schmitt, who is also a famous philosopher and playwright.The love discourse is revealed in the description of characters that differ by their age, social and gender status, and also through the type of the relations between the partners. The basic principles of construction of discourse of love as well as the general and specific features of actualization of discourse of love with each couple presented in the discussed novel are defined. The love discourse in the novel Les Perroquets de la Place d’Arezzo by Eric-Emmanuel Schmitt has proved to be typical postmodern discourse with some elements of romantic fiction.